ETIKA PROFESI DAN TANTANGAN DALAM DUNIA KERJA MODERN: PERSPEKTIF MAHASISWA AKUNTANSI - Johan, Raissa Artanti; Muzzainah, Muzzainah; Fitriyanih, Nurkhalishah; Syahbani, Firdaus (Universitas Trilogi, 2025)
The development of the modern world of work which is characterized by digitalization, globalization, and organizational pressure raises new ethical challenges for professionals, including accountants. This study aims to examine accounting students' understanding of professional ethics and their perceptions of ethical challenges in today's workplace. Using a descriptive qualitative approach, data were obtained through an open-ended essay questionnaire distributed to final year accounting students. The results of thematic analysis revealed three main themes: (1) students' understanding of the importance of professional ethics as a moral foundation; (2) challenges faced in the modern workplace such as target pressure, technological developments, and ethical conflicts; and (3) students' readiness in facing ethical dilemmas, including the role of higher education in shaping professional character. The findings show that although students have a good understanding of ethics, they also realize the gap between theory and practice. Keywords: Professional Ethics; Accounting Students; Workplace Challenges; Digitalization; Ethics Education